(untitled) (Journal of Applied Learning and Teaching, 2021)
Campus climate surveys are effective ways to assess behaviors and attitudes regarding sexual misconduct. Undergraduate applied learning and research-centered projects are also integral to helping students apply textbook content to real-world dilemmas. In conjunction with the Collaboration for Assault Response & Education Office and the Office of Title IX and Clery Compliance, the researchers taught and mentored undergraduate students in co-facilitating a sexual misconduct assessment. The project proceeded in four phases: planning and training; focus group recruitment; focus group facilitation; and data analysis. This research highlights how university and college departments, as well as organizations, can collaborate to facilitate large-scale assessments. We also explain how these assessments can be integrated into applied learning and research projects for students. Opportunities for future research include more extensive training on qualitative data collection and analysis for undergraduate students; routine assessments of the campus climate related to sexual misconduct; and continued student-centered research opportunities that focus on current events.